The perceptions of trainee teachers in B.Ed TESL Programme in UiTM on the application of drama techniques in improving speaking skills in ESL teaching / Ahmad Ariffuddin Yusof - Yusof, Ahmad Ariffuddin (Faculty of Education, 2014)
This study investigated trainee teachers' general perception on the application of drama techniques in improving speaking skill in ESL teaching, the relationship between speaking skill and drama, and the ways and suggestions that can be used towards the implementation of drama based pedagogy in teaching speaking skill. Questionnaires were distributed among 60 trainee teachers comprised of final year students in B.Ed TESL Programme in UiTM. Data was tabulated using frequencies and descriptive analyses. Based on the data, drama techniques are an interesting alternatives to the traditional way of teaching English, because it can boosts the motivation of the students in seeking knowledge and drama techniques also promote cooperative and collaborative learning. The data also showed that drama techniques are an effective tool for pronunciation teaching and that drama techniques can increase the level of students' oral competence. In the implementation of drama based pedagogy in the teaching speaking classroom, the Ministry of Education plays a big role in terms of introducing more courses on making sure teachers are efficient in its implementation, while the teachers should be effective and creative and being prepared to employ drama based activities.